Nutritional value and chemical properties of drone milk as a source of probiotics and evaluation of antioxidant effects on reproductive structures by in vitro test - Kačániová, Miroslava; Škultétyová, Mária; Tvrdá, Eva; Benko, Filip; Ďuračka, Michal; Čmiková, Natália; Ivanišová, Eva; Havlík, Jaroslav; Zaguła, Grzegorz; Carbonell Barrachina, Angel Antonio; Garzoli, Stefania (Process biochemistry (1991), 2025)
The objective of this study was to compare the probiotic bacteria present in drone milk (DM) and drone larvae (DL). Furthermore, the study aimed to investigate the antibacterial capacity against Staphylococcus and Streptococcus species isolated from animal semen. The in vitro effects of DM and DL on male reproductive cells and rabbit tissues were examined. In addition, the nutritional and chemical composition of both bee products was investigated. Fresh and freeze-dried samples were used to isolate probiotic bacteria identified by MALDI-TOF MS Biotyper. Lactobacilli, especially Apilactobacillus kunkeii, Lactiplantibacillus pentosus, Lactiplantibacillus plantarum, and Secundilactobacillus malefermentas, received the highest identification scores. The best results were observed when targeting S. aureus, S. epidermidis, and S. vitulinus. The freeze-dried materials were tested on rabbit spermatozoa and testicular fragments to ascertain the effects of DM and DL. The results showed that the samples significantly reduced the amount of reactive oxygen species in the reproductive structures which resulted in a decrease in lipid peroxidation. Furthermore, testicular fragments treated in vitro with DM and DL produced considerably more testosterone and cholesterol; crude protein, nitrogenous compounds and fat were all present in higher amounts in DL while the content of reducing sugars was higher in DM. [Display omitted] •The main chemical components of drone milk affect biological activity.•Drone milk showed antimicrobial activity against Staphylococcus and Streptococcus genus.•Drone milk has probiotic effects.•Drone milk affects rabbit spermatozoa.•Effects in vitro of drone milk on rabbit testicular fragments.